Tailoring the texture of an extruded Mg sheet through constrained groove pressing for achieving low mechanical anisotropy and high yield strength. (September 2020) - Hoseini-Athar, M.M.; Mahmudi, R.; Prasath Babu, R.; Hedström, P.
Abstract: Constrained groove pressing (CGP) was utilized to modify the texture and mechanical properties of extruded Mg–2Gd–3Zn sheet with typical TD (transverse direction)-split texture and pronounced mechanical anisotropy. The texture evolution sequence during CGP was studied and it was observed that a new 〈 1 ¯ 2 1 ¯ 1 〉 component with basal poles rotated 15°–30° toward the extrusion direction (ED) is introduced during CGP, as a result of simultaneous activation of basal and prismatic slip and shear deformation. Finally, a non-basal ED–TD double split texture was obtained after the CGP process, resulting in significantly reduced mechanical anisotropy. Graphical abstract: Image, graphical abstract